Fixing Exchange Rate of Currency Units Within the Frames of the Effective Monetary System - Yu. A. Kropin (Plekhanov Russian University of Economics, 2019)
In current conditions of unstable global currency system and spoilt reputation of the American dollar the possibility to pass over to national currency in settlements among countries has become very topical. Thus the issue of fixing the exchange rate of currency units has become very important.  The article reveals the problem from the positions of the Russian school of economic thought, which is critical concerning the opinion of neo-liberal school about fixing the exchange rate of currency units. The focus is made on the fact that today’s method of estimating the exchange rate is ungrounded. The author puts forward the way of estimating the exchange rate, which can meet the essence of the present monetary system. To reveal the subject of the research and present the material the author used methods from general to particular, deduction and induction, natural sequence and some others. As a result a conclusion was made that fixing the exchange rate of currency units should be grounded on the one hand, by factors of the fundamental order, i. e. the level of social and economic development of the country, and on the other hand – by the current market situation on market of those goods, which are exported from the country and those commodity goods, which are imported to the country.